The Price Effect of Tariff Liberalization: Measuring the Impact on Household Welfare - Nicita, Alessandro (2012)
Trade policy literature has for many years emphasized open policies positive impact on economic growth and development. While these results generally hold when measured on averages, empirical evidence suggests that trade liberalization is unlikely to produce beneficial results across all households. This study adds to the literature by providing an analysis of the distributive effects of tariff liberalization in Mexico. The paper examines the effect of tariff liberalization from the perspective of households both as consumers and factor owners allowing for imperfect domestic price transmission. The results indicate the overall positive effect of tariff liberalization masks significant differences in the distribution of gains both across income levels and across geographic regions. Richer households are found to have gained relatively more. Urban areas, as well as Mexican states closest to the United States border, are also found to be larger beneficiaries while southernmost states have been largely bypassed by the effects of tariff liberalization. Those results can be explained not only in relation to the different endowments of the households, but also by the diverse effects on local prices that has resulted from Mexican trade liberalization.